Calibration of the liverwort confluence in the left leads by neoplastic biliary obstructions - Praderi, Raúl C.; Estefan, Alberto (Cirugía del Uruguay, 1975)
A new surgical procedure is presented for the palliative treatment of pedicular malignant biliary obstruction: intubation of the hepatic ducts confluence in the left bypass operations by a right trans-hepatic tube, either a simple one or an U-tube. Its aim is to preserve drainage of both hemi-livers when the progression of the tumour infiltrates the aforesaid confluence. Maintenance of its viability avoids biliary stasis and severe angiocholitis in the contralateral undrained lobe, which shortens and complicates survival. Four cases were thus treated: three anastomosis in the left hepatic duct and one in the duct of segment 111. The post-operative courses were uneventful and average survivals of over 10 months were obtained, without relapse of jaundice or bouts of angiocholitis.